Titanium nitride layer formation by TIG surface melting in a reactive environment - Mridha, Shahjahan (Elsevier, 2005)
The possibility of forming a hard titanium nitride layer has been studied by melting commercial purity titanium (CP-Ti) surfaces beneath the tungsten inert gas (TIG) torch in a pure nitrogen environment. The surface melting of titanium with TIG torch of energy densities ranging from 46 MJm−2 to 182 MJm−2 produced a melt layer of over 1mmthickness. The topographies of the molten tracks glazed at energy densities above 68 MJm−2 had rippling marks and they are perpendicular to the glazing direction. However, the tracks glazed at lower energy densities of 46 MJm−2 and 55 MJm−2, produced cellular type surface structures. Porous edges were present in all the tracks glazed in the nitrogen environment at different energy densities. Those tracks glazed at higher energy densities created surface cracking along the track width, and they propagated down to the melt zone. The track cross sections gave irregular melt profiles; the Maragoni force that produced high nitrogen concentration fluid along the convectional flow lines and the exothermic reaction for the formation of titanium nitride (TiN) are presumed to be responsible for creation of such irregular melt features. The resolidified melt microstructures contained non-uniform distribution of dendrite populations. The XRD analysis at different depths of the melt cross section revealed that the titanium nitride phase dominates the melt pool microstructure. The tracks gave a surface hardness of around 2000HV. All the tracks glazed at different energy densities produced hardness profiles with gradual decrease in hardness at a higher melt depth. This indicates that the hardness development is directly related to the dendrite population in the melt pool, which was found to decrease at deeper depths because of the lower concentration of nitrogen.